Design of Sliding Correlator Channel Sounder for Ionospheric Channel Probing Based on Software Define Radio - Varuliantor Dear; Adi Purwono; Iskandar Iskandar; Adit Kurniawan; Prayitno Abadi (Buletin Pos dan Telekomunikasi, 2021)
Observation of wireless channel using channel sounder method is needed in order to obtain the channel characteristics in the form of delay spread (Tm) and doppler spread (fD) parameters for optimizing the design of digital communication systems. This also applies to the ionosphere channels which are known to have dynamic properties in the time and place domains. The Sliding Correlator Channel Sounder technique known as a popular technique due to the advantage in the low level of complexity and relatively low cost. Similar to the advantages of the sliding correlator technique, Software Define Radio (SDR) device is one of the popular inexpensive platforms for implementing the communication system into the real world. The implementation of the sliding correlator channel sounder technique in the SDR platform will increase the advantages of the ionosphere channel measurement system that needed as an effort to obtain the dynamic of ionospheric channel characteristic information. However, the process of implementing a sliding correlator channel sounder system into the SDR device requires precise calculations to guarantee the designed system able to works according to the specifications of the SDR device and also meet the system performance targets. This paper discusses the design of a sliding correlator channel sounder system for observing the characteristics of ionosphere channels using SDR devices. The system design starts with the process of calculating the clock frequency generator bit (fchirp) based on the system performance target which refers to the recommendation of the ionospheric channel characteristics based on ITU-R F.1487 documents. Parallel with the calculation of the fchirp, the calculation of the Pseudo Noise (PN) bit length (L) based on the Dynamic Range (DR) value that meets with the specifications of the SDR hardware also carried out. Based on the obtained fchirp and L values, the calculation of other sliding correlator channel sounder parameters is performed with a limitation of a hardware specification and the target system performance. MATLAB simulation results show that the expected system performance can be met. This systems can also be realized significantly through the results of real signal transmission experiments conducted in a closed room laboratory